Cigarette Graphic Warning Labels Are Not Created Equal: They Can Increase or Decrease Smokers’ Quit Intentions Relative to Text-Only Warnings - Evans, Abigail T (Nicotine Tob Res, 2017)
INTRODUCTION: Cigarette graphic-warning labels elicit negative emotion. Research suggests negative emotion drives greater risk perceptions and quit intentions through multiple processes. The present research compares text-only warning effectiveness to that of graphic warnings eliciting more or less negative emotion. METHODS: Nationally representative online panels of 736 adult smokers and 469 teen smokers/vulnerable smokers were randomly assigned to view one of three warning types (text-only, text with low-emotion images, or text with high-emotion images) four times over 2 weeks. Participants recorded their emotional reaction to the warnings (measured as arousal), smoking risk perceptions, and quit intentions. Primary analyses used structural equation modeling. RESULTS: Participants in the high-emotion condition reported greater emotional reaction than text-only participants (b(Adult) = 0.21; b(Teen) = 0.27, p’s < .004); those in the low-emotion condition reported lower emotional reaction than text-only participants (b(Adult) = −0.18; b(Teen) = −0.22, p’s < .018). Stronger emotional reaction was associated with increased risk perceptions in both samples (b(Adult) = 0.66; b(Teen) = 0.85, p’s < .001) and greater quit intentions among adults (b(Adult) = 1.00, p < .001). Compared to text-only warnings, low-emotion warnings were associated with reduced risk perceptions and quit intentions whereas high-emotion warnings were associated with increased risk perceptions and quit intentions. CONCLUSION: Warning labels with images that elicit more negative emotional reaction are associated with increased risk perceptions and quit intentions in adults and teens relative to text-only warnings. However, graphic warnings containing images which evoke little emotional reaction can backfire and reduce risk perceptions and quit intentions versus text-only warnings. IMPLICATIONS: This research is the first to directly manipulate two emotion levels in sets of nine cigarette graphic warning images and compare them with text-only warnings. Among adult and teen smokers, high-emotion graphic warnings were associated with increased risk perceptions and quit intentions versus text-only warnings. Low-emotion graphic warnings backfired and tended to reduce risk perceptions and quit intentions versus text-only warnings. Policy makers should be aware that merely placing images on cigarette packaging is insufficient to increase smokers’ risk perceptions and quit intentions. Low-emotion graphic warnings will not necessarily produce desired population-level benefits relative to text-only or high-emotion warnings.